2020
DOI: 10.1007/s10008-020-04800-1
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical quartz crystal microbalance study of magnesium porphine electropolymerization process

Abstract: Material and charge balances in the course of the electropolymerization process of the non-substituted Mg(II) porphine (MgP) at a low oxidation potential from its acetonitrile solutions of various concentrations have been studied via the in situ electrochemical quartz crystal microbalance method (EQCM). Thus, registered electrode mass increase due to the MgP oxidation at its surface has been used, in combination with in situ spectroelectrochemical data, for determination of the key parameters of the polymeriza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…Besides, a detailed analysis and simulation of the isotopic patterns that where observed on the mass spectrum confirmed that only one bond was observed between two monomer units. Moreover, UV-visible spectroelectrochemistry [30] and electrochemical quartz crystal microbalance [31] experiments demonstrated that the number of covalent bonds varies from 2.2 to 2.4 per monomer unit. That means that type 1 polymer exhibits mainly a linear and/or a zig-zag arrangement, with only sporadic ramification centers.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, a detailed analysis and simulation of the isotopic patterns that where observed on the mass spectrum confirmed that only one bond was observed between two monomer units. Moreover, UV-visible spectroelectrochemistry [30] and electrochemical quartz crystal microbalance [31] experiments demonstrated that the number of covalent bonds varies from 2.2 to 2.4 per monomer unit. That means that type 1 polymer exhibits mainly a linear and/or a zig-zag arrangement, with only sporadic ramification centers.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the use of QCMs with dissipation monitoring allows to study emerging applications in greater detail. Reported applications range from metal electrodeposition [15,16] and leaching studies [17], ion dynamics [18], porous solids characterization [19], organic electropolymerization [20,21] to for example monitoring self assembled monolayer formation [22]. The versatility of (E) QCM measurements lends it very well to combinations with other complementary techniques like in situ spectroscopic ellipsometry [23], surface plasmon resonance [24,25], scanning probe microscopy [26,27] or Fourier-transform infrared spectroscopy [28,29].…”
Section: Introductionmentioning
confidence: 99%